The Effectiveness of Smokescreen Program on Smoking Prevention and Cessation - Aghnia Kamila; Teuku Tahlil; Elly Wardani (Universitas Muhammadiyah Semarang, 2021)
Smoking is deviant behavior that often affects adolescents and is addictive. The prevalence of smoking among adolescents is relatively high and harms health, so prevention efforts are needed. This study aims to know the smokescreen program's effectiveness on smoking prevention and cessation among students at Madrasah Tsanawiyah in Banda Aceh. The method used in this research is a quantitative quasi-experimental model with a non-equivalent control group design. This study's population was all students of class VII and VIII in two Madrasah Tsanawiyah in Banda Aceh, totaling 1221 students, and the sample was selected by purposive sampling technique as many as 302 respondents. Data was collected online using Zoom and Google Form and then analyzed using SPSS with univariate and bivariate analysis. The results showed differences in effectiveness in smoking prevention and cessation (ρ-value 0.000 <0.05) in students before and after being given the smokescreen program intervention. The majority of students have strong self-efficacy, as much as 86.8%. Thus, this study also concluded that the smokescreen program effectively prevented and stopped smoking behavior among students. For this reason, schools can facilitate students in increasing knowledge about cigarettes by watching videos and playing games so that students' self-efficacy increases.